Peran Dinas Pekerjaan Umum, Penataan Ruang dan Pertanahan Provinsi Kepulauan Riau dalam Pembangunan Infrastruktur Kawasan Gurindam Dua Belas Kota Tanjungpinang - Raissa Syahrina Desmarianti; Nazaki Nazaki; Rizky Octa Outri Charin (Fakultas Teknik Universitas Cenderawasih, 2025)
Tanjungpinang City has been the capital of Riau Islands Province since 2002 based on Law Number 5 of 2001 concerning the Establishment of Tanjungpinang City, which also became the basis for the establishment of Riau Islands Province in 2002 through Law Number 25 of 2002 concerning the Establishment of Riau Islands Province. Tanjungpinang City has a very strategic location for tourism, as evidenced by the large number of foreign tourists visiting the city. However, infrastructure in Tanjungpinang City at that time seemed to be stagnant, unable to be developed further due to the lack of efforts from the local government. Responding to this phenomenon, the Riau Islands Provincial Government, through the Office of Public Works, Spatial Planning and Land (DPUPP), has stepped in as the government agency responsible for sustainable infrastructure development in the construction and planning of the Gurindam Dua Belas Area. This development and planning will involve all relevant sectors, especially agencies/OPDs that will work together in an integrated manner, as well as the involvement of the community and the private sector as investors in this area. This study aims to describe and analyze the role of the Riau Islands Provincial Public Works, Spatial Planning and Land Agency in Infrastructure Development in the Provincial Capital. The research method used was qualitative research with data collection techniques in the form of literature studies, interviews, and observations.